A Liquidity, Capital Intensity and Tax Aggressiveness: Profitability as a Mediating Role - Mas’adah, Mas’adah; Sulistiowati, Rina; Nataliawati, Rita; Hakim, Mesra Berlyn; Qosim, Qosim (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This research aims to examine the influence of Liquidity, Capital Intensity on Tax Aggressiveness mediated by Profitability. The data used is archival data, namely secondary data obtained from the Indonesian Stock Exchange (https://www.idx.co.id/). The sample in this study refers to the financial statements of all companies listed on the Indonesia Stock Exchange during 2018-2022, namely 864 companies. The final sample in this research was 99 companies and the total final sample was 495 samples. The research results show that liquidity has a positive and significant effect on tax aggressiveness. Capital Intensity has a positive and significant effect on Tax Aggressiveness. Profitability has a significant effect on Tax Aggressiveness. Furthermore Profitability mediates the complete (complete mediation) effect of Liquidity on Tax Aggressiveness and Profitability mediates the partial (partial mediation) effect of Capital Intensity on Tax Aggressiveness